Assessing the Genetic and Environmental Factors on Egg Amino Acid Traits in Chickens: A Review - Dipson Gyawali; Tatsuhiko Goto (Animals)
Eggs are good sources of animal proteins. Methods for creating designer eggs are attractive to scientists and producers of the eggs, in order to fulfill customers’ demands. We review and summarize the current understanding of how genetic and environmental factors influence chicken egg components, specifically, amino acid contents of yolk and albumen. Genetically diverse breeds of chicken enable us to obtain a wide variety of egg amino acids. Moreover, the use of fermented feed and different rearing systems (barn and deep litter) has impacts on egg amino acids, which may be mediated through changes in the intestinal environment, including the microbiota. To overcome the future food crisis, the combinations of breeds, feeds, and rearing systems will be important for producing designer eggs. In the future, not only long-term selected layer strains will be required, but also many kinds of indigenous chicken breeds, which have already adapted to each local environment in the world, should be investigated under the continental levels of climate environment using different fermented feed materials. To better understand the interplay between genetic and environmental factors, we will offer valuable insights for both egg producers and consumers, potentially guiding future efforts to optimize egg amino acid contents in chickens.